THE EFFECTS OF TRANSPORTATION ON IMMUNE MODULATION OF WILD AND OCEAN-RANCHED GREENLIP ABALONE (Haliotis laevigata) - Sri Rahayu Setyaningsih; Ravi Fotedar; Roy Melville-Smith; Ishaaq Saputra; Nelson Fernandez; Subas Adhikari (Indonesian Aquaculture Journal, 2020)
The effects of live transportation on the immune modulation of wild and ocean-ranched greenlip abalone (Haliotis laevigata) were evaluated. Samples of abalone were collected both in autumn and winter in Flinders Bay, Augusta, Western Australia, and land transported for 6 (six) hours. Several immunological parameters were assessed, including survival rate, total haemocyte count, osmoregulatory capacity, phagocytic rate, lactate level, and glucose level. The results indicated that the abalone samples collected in the two seasons showed different physiological responses; the winter samples were more responsive to transportation than the autumn samples. Transportation stress significantly increased total haemocyte count and osmoregulatory capacity of the winter samples, suggesting an immune stimulation. This stress also triggered an immune suppression, causing the phagocytic rate and lysosomal stability to significantly decrease after transportation. Lactate levels in the winter samples decreased significantly after transportation, possibly indicating the transition from a stressed to normal state, during the period of recovery. The constant level of glucose before and after transportation in both seasons showed that it was the least sensitive indicator used in this study. In general, there was no difference in the immune modulation parameters between wild and ranched abalone in either of the seasons sampled. However, in the autumn samples, there were significant differences (P<0.05) in haemocyte count and osmoregulatory capacity of the wild and ranched samples collected from all sites. These differences did not form a consistent indicator trend between the sites from the two sample sources. Therefore, the results do not raise any immediate concern that ranched abalone were differently stressed to those from the wild. The results in present study could serve as useful data in developing the live transportation method of greenlip abalone.